Peace education as a panacea for achieving goals of education for all (EFA) in Nigeria (2004)
This paper examines the role of peace education as a panacea for the attainment of the six goals of Education For All (EFA) by 2015. The paper looks at the goals of EFA, as stated at the Jomtien conference of 1990, in meeting basic learning needs, so as to develop self-reliance in meeting the complexity of societal changes. The presently applied strategies for achieving goals of EFA are not achieving much; there is the need to make progress towards the achievement of EFA by 2015. The introduction of the concept of peace education within the circumstances in which EFA is to operate is seen as a plausible solution to the problems confronting EFA. The paper sees the use of content of peace education and the development of skills and attitudes in peace education in providing good and conducive learning environment. Furthermore, peace education will foster the development of learners to live and work in dignity, participate in developmental programmes, valuing of all opinions and establishment of processes for compromise and negotiation. The paper concludes that education for peace will produce assertive citizens who will individually and collectively be committed to autonomy of thought and action, eradication of culture of violence and development of material base that are necessary for realizing the goals of EFA.